A probe into Confucius’s ‘unusable’ in “The Hereditary House of Confucius”, records of the grand historian - Ser, Wue-Hiong; Lee, Loo-Yee (College of International Studies and Social Sciences, National Taiwan Normal University, 2022)
“The Hereditary House of Confucius” 孔子世家 compiled by Sima Qian司馬遷based on pre-Qin documents is the first full biography of Confucius in history. However, it has been questioned and criticized by academia in the past century, mainly focus on its historical facts and interpretation of material. The way to interpret “The Hereditary House of Confucius” has become a significant issue in this modern times. This paper serves “The Hereditary House of Confucius” as a narrative text structure and reinterprets the narrative of Confucius based on the clues of ‘unusable’ 不用 that appear frequently. It was found that Sima Qian consciously used ‘unusable’ to highlight the turning point of the storyline to metaphor the eagerness of Confucius in ‘seeking for use’ 求用. The intertwined clues of ‘seeking for use’ and ‘unusable’ show Confucius's personality traits, who desperately wanted to carry out the principle but ended up with an unusable tragic fate. When going through tough times, a prophet's image of Confucius was gradually shaped by his extraordinary persevere personality. Since Confucius could not make a difference in his time, he embeds his thought in the Spring and Autumn Annals 春秋in order to pass down the great ideal to the future generation. In conclusion, the context of “The Hereditary House of Confucius” will be gradually clear and coherent when reading with the clue of ‘unusable’.